Fun, Taste, & Games: An Aesthetics of the Idle, Unproductive, and Otherwise Playful - Sharp (MIT Press, 2019)
Monograph
fulltext
Keywords: Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing; General Topics for Engineers